Recent Research Advances in Small-Molecule Pan-PIM Inhibitors - Xu, Lei; Meng, Yu-Cheng; Guo, Peng; Li, Ming; Shao, Lei; Huang, Jun-Hai (Pharmaceutical Fronts, 2022)
PIM kinase is consequently emerging as a promising target for cancer therapeutics and immunomodulation. PIM kinases are overexpressed in a variety of hematological malignancies and solid tumors, and their inhibition has become a strong therapeutic interest. Currently, some pan-PIM kinase inhibitors are being developed under different phases of clinical trials. Based on the different scaffold structures, they can be classified into various subclasses. The X-ray structure of the kinase complex outlines the rationale of hit compound confirmation in the early stage. Structure–activity relationships allow us to rationally explore chemical space and further optimize multiple physicochemical and biological properties. This review focuses on the discovery and development of small-molecule pan-PIM kinase inhibitors in the current research, and hopes to provide guidance for future exploration of the inhibitors.
Keywords: pan-PIM inhibitors; structure classification; lead optimization; structure–activity relationship